2022
DOI: 10.3934/energy.2022002
|View full text |Cite
|
Sign up to set email alerts
|

Policies and laws in the application of renewable energy Indonesia: A reviews

Abstract: <abstract> <p>Renewable energy is a global energy system that is very important in nature and humans' harmonious and conducive development. Considerable attention from the government towards renewable energy is due to the increasing energy demand. The impact of the current energy shortage has also resulted in damage to the environment. The current legal framework for accelerating the development of renewable energy has made a considerable contribution but is still not in favor of investors. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 83 publications
0
16
0
1
Order By: Relevance
“…However, renewable energy development in the Philippines faces several challenges, including high upfront costs, regulatory barriers, and grid integration issues [18]. Although the government has its fair share of renewable energy-based projects, implementations are limited to a few areas [19]. Therefore, expanding sustainable green technologies is a prerequisite to achieving a nationwide shift from fossil-fueled energies to renewable energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…However, renewable energy development in the Philippines faces several challenges, including high upfront costs, regulatory barriers, and grid integration issues [18]. Although the government has its fair share of renewable energy-based projects, implementations are limited to a few areas [19]. Therefore, expanding sustainable green technologies is a prerequisite to achieving a nationwide shift from fossil-fueled energies to renewable energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…The extracted oil has a lower viscosity, high volatility, and higher oxygen content. 35,36 These thermo-physical properties support its use to replace diesel in existing diesel engines.…”
Section: Pine Oilmentioning
confidence: 94%
“…It was found that citronella oil exhibited peak heat release compared to diesel fuel due to the better evaporation of the low viscous citronella oil. In terms of emission reduction in diesel engines, NOx emission was a major concern in CNO blends, 35 with many researchers working towards NOx elimination from biodiesel/biofuel. 79−80 There were many routes found such as water emulsion, nanoemulsion, nano-additive, SCR, EGR, etc.…”
Section: Lemon Peel Oilmentioning
confidence: 99%
“…The availability of solid biomass waste that can be converted into energy is relatively abundant, as reported in previous publications [1][2][3][4][5][6][7][8][9]. Policies related to the use of renewable energy implemented by the government are the proper steps to advance the development and development of renewable energy nationally [10][11][12][13][14][15]. Meanwhile, various technologies to support renewable energy development have also been developed [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%